The strawberry transcription factor FaRAV1 positively regulates anthocyanin accumulation by activation of FaMYB10 and anthocyanin pathway genes. Issue 11 (13th April 2020) - Zhang, Zuying; Shi, Yanna; Ma, Yuchen; Yang, Xiaofang; Yin, Xueren; Zhang, Yuanyuan; Xiao, Yuwei; Liu, Wenli; Li, Yunduan; Li, Shaojia; Liu, Xiaofen; Grierson, Donald; et al.
Summary: The RAV (related to ABI3/viviparous 1) group of transcription factors (TFs) play multifaceted roles in plant development and stress responses. Here, we show that strawberry ( Fragaria × ananassa ) FaRAV1 positively regulates anthocyanin accumulation during fruit ripening via a hierarchy of activation processes. Dual‐luciferase assay screening of all fruit‐expressed AP2/ERFs showed FaRAV1 had the highest transcriptional activation of the promoter of FaMYB10, a key activator of anthocyanin biosynthesis. Yeast one‐hybrid and electrophoretic mobility shift assays indicated that FaRAV1 could directly bind to the promoter of FaMYB10 . Transient overexpression of FaRAV1 in strawberry fruit increased FaMYB10 expression and anthocyanin production significantly. Correspondingly, transient RNA interference‐induced silencing of FaRAV1 led to decreases in FaMYB10 expression and anthocyanin content. Transcriptome analysis of FaRAV1 ‐overexpressing strawberry fruit revealed that transcripts of phenylpropanoid and flavonoid biosynthesis pathway genes were up‐regulated. Luciferase assays showed that FaRAV1 could also activate the promoters of strawberry anthocyanin biosynthetic genes directly, revealing a second level of FaRAV1 action in promoting anthocyanin accumulation. These results show that FaRAV1 stimulates anthocyanin accumulation in strawberry both by direct activation of anthocyanin pathway gene promoters and by up‐regulation of FaMYB10, which also positively regulates these genes.